Spillover of Trypanosoma lewisi and Trypanosoma musculi Allied Trypanosomes from Rodents to Bats in the Roofs of Human Dwellings: Synanthropic Bats as a Potential New Source of Human Opportunistic Trypanosomes - Evaristo Villalba-Alemán; Luciana Lima; Paola Andrea Ortiz; Bruno Rafael Fermino; Gladys Elena Grisante; Carla Monadeli Filgueira Rodrigues; Letícia Pereira Úngari; Néstor Añez; Herakles Antonio Garcia; Marta Maria Geraldes Teixeira (Zoonotic Diseases)
Bats and rodents serve as reservoirs for numerous zoonotic pathogens, including species of Trypanosoma and Leishmania. Domestic rats host the flea-transmitted Trypanosoma (Herpetosoma) lewisi, which can be associated with humans, particularly young or immunocompromised individuals. Using Fluorescent Fragment Length Barcoding (FFLB) and phylogenetic analyses based on SSU rRNA sequences, we identified two Herpetosoma species, T. lewisi-like and T. musculi-like species, in bats of different families inhabiting rooftops and peridomestic structures in Brazil (44%, 107 bats examined) and Venezuela (50%, 52 bats examined). These species are typically associated with Rattus spp. (domestic rats) and Mus musculus (house mice), respectively. Furthermore, bats were co-infected with up to five other species, including Trypanosoma dionisii, Trypanosoma cruzi marinkellei, and isolates from the Trypanosoma Neobat clade, all strongly associated with bats, and Trypanosoma cruzi and Trypanosoma rangeli, known to infect various mammals, including humans. Therefore, our findings expand the known host range of Herpetosoma to bats, marking the first report of potential spillover of Herpetosoma trypanosomes from rodents to bats and underscoring the potential for the cross-species transmission of flea-borne trypanosomes. These results highlight the need for a One Health approach to assess infection risks associated with trypanosome spillover from synanthropic rodents and bats to humans.